2008
DOI: 10.1534/genetics.108.093898
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Back Talk With Evolutionary Implications: Stimulation of the Drosophila Sex-Determination Gene Sex-lethal by Its Target transformer

Abstract: We describe a surprising new regulatory relationship between two key genes of the Drosophila sexdetermination gene hierarchy, Sex-lethal (Sxl) and transformer (tra).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…The Drosophila system seems to be a derivative of the ancestral tra-based system in which the key functions, selection and maintenance of the sexual fate, are both delegated to Sxl. It has been proposed that Sxl was initially recruited as an additional coregulator of tra premRNA splicing, thereby establishing a functionally redundant circuit to tra autoregulation (Siera and Cline 2008). In this context, Sxl may have gradually relieved tra from upholding the female mode of its splicing to become eventually the exclusive regulator of tra.…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila system seems to be a derivative of the ancestral tra-based system in which the key functions, selection and maintenance of the sexual fate, are both delegated to Sxl. It has been proposed that Sxl was initially recruited as an additional coregulator of tra premRNA splicing, thereby establishing a functionally redundant circuit to tra autoregulation (Siera and Cline 2008). In this context, Sxl may have gradually relieved tra from upholding the female mode of its splicing to become eventually the exclusive regulator of tra.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, Sxl has been recruited upstream of tra and is female specifically regulated through its own auto regulatory loop. However, Siera and Cline [61 ] showed that tra auto regulation may also be ancestral in Drosophila since a positive feedback loop of tra still operates through Sxl, which in turn regulates tra splicing. Tra regulation by X chromosome dose may occur outside the Drosophilidae but most likely in the absence of Sxl.…”
Section: Doublesexmentioning
confidence: 99%
“…Sxl orthologs have been identified in insects as diverse as aphids, moths, beetles, and mosquitoes; however, outside of the family Drosophilidae, there seems to be no obvious somatic difference in Sxl expression level or products between the sexes and/or no DNA homologies to the key structural elements in Drosophila Sxl that are responsible for its female-specific functioning (referenced in Traut et al 2006; and see Siera and Cline 2008 for Scaptodrosophila lebanonensis). In most insects, the transformer gene seems to occupy the position of Sxl as the master feminizing switch gene that responds to sex determination signals and epigenetically maintains the sexually determined state through a positive feedback loop on pre-mRNA splicing Gempe et al 2009;Hediger et al 2010;Verhulst et al 2010).…”
Section: T He X Chromosome Counting System Used Bymentioning
confidence: 99%